Dukungan Keluarga Dengan Kualitas Hidup Pada Pasien Kanker Payudara Yang Menjalani Kemoterapi - Cahyono, Hendra Dwi; Ira, Ni Putu; Prasetyo, Hendro (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2023)
Background:Cancer is one of the main causes of death in the world. The incidence of breast cancer is the second highest in the world. The many impacts ofchemotherapy treatment that is undertaken, will become a long-term problem that will affect the patient's qualit y of life. Unfavorable psychological conditions due to chemotherapy make cancer patients need support from the closest people, the family is the patient's closest person who will provide comfort and peace. Objective:To analyze the effect of family support on the quality of life of breast cancer patients undergoing chemotherapy Methods: The method of this study is correlated with a cross-sectional approach. with 86 samples using a non-probability sampling technique with consecutive sampling and using a measuring instrument used on variables using a questionnaire. Results:The results of the analysis using the Spearman Rank Tests ? 0.05 obtained a p-value (0.00 <? (0.05). Conclusion:There is a relationship between family support and quality of life in breast cancer patients undergoing chemotherapy at Level III Hospital Baladhika Husada Jember. Family support is one of the factors that have a positive contribution to the quality of life of cancer patients. The family support provided can be in the form of attention or an active role in the treatment and therapy programs being undertaken by breast cancer patients. Involvement of family members in motivating to maintain the condition and perform chemotherapy